The Path of Cicely Saunders: The "Peculiar Beauty" of Palliative Care. Issue 1 (January 2020) - Miccinesi, Guido; Caraceni, Augusto; Garetto, Ferdinando; Zaninetta, Giovanni; Bertè, Raffaella; Broglia, Chiara M.; Farci, Bruno; Aprile, P. Lora; Luzzani, Massimo; Marzi, Annamaria M.; Mercadante, Sebastiano; Montanari, Luigi; et al.
This paper is aimed at focusing on the writings and the experience of the Hospice movement Founder, Dame Cicely Saunders. The in-depth analysis carried out had the objective of verifying if "the way" of Cicely to understand, live and propose palliative care was still current and "beautiful", so that we can nowadays refer to her fascinating "Original Palliative Care". With "beauty" we mean, on the one hand, a way able to allow a personal path of research of the meaning of the disease and of the care, both for those who care and for those who are cared for. On the other hand, it seems to us that Cicely strongly suggests how this path can not be carried out alone, but is only possible within the context of a network of relationships and support, in a so called "relational autonomy", for the patient, included in a "care ethics". The authors believe that the work extensively documents as the overall approach of Cicely, traditional but always to be rediscovered, is still today the most convincing way of conception and action of palliative care.